Kajian Hukum Tindak Pidana Cyber Phising Ditinjau Dari Undang-Undang Nomor 27 Tahun 2022 Tentang Data Pribadi - Putu Ryanniva Karenina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to evaluate the effectiveness of implementing Law Number 27 of 2022 concerning Personal Data Protection in Indonesia's efforts to prevent and combat phishing crimes. This research employs a normative legal method to analyze the implementation of the PDP Law in the context of preventing and combating phishing crimes. The findings indicate that the PDP Law has provided a comprehensive legal framework for protecting personal data, including data that is often targeted by phishing attacks.The implementation of the PDP Law is overseen by the Personal Data Protection Authority, which has the authority to impose administrative sanctions, support law enforcement processes, and evaluate cross-border data transfers. To achieve maximum effectiveness in combating phishing crimes, strong synergy is needed between the government, private sector, and the public. The PDP Law has provided a good legal framework, but the success of its implementation is highly dependent on the commitment of all parties to work together in protecting personal data.